Low-temperature anomalies in the magnetic and thermal properties of molecular cryocrystals doped with oxygen impurity: Low-Temperature Physics and Chemistry in Cryomatrice - Freiman, Yu. A.; Tretyak, S. M.; FACE=\\\"Arial\\\">żowski, A. Je<FONT (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2000)
The magnetic properties of oxygen pair clusters are investigated theoretically for different cluster geometries which can be realized by doping molecular cryomatrices with oxygen. Anomalous temperature and pressure behavior of the magnetic susceptibility, heat capacity, and entropy is predicted. It isproposed to use these anomalies for studying the parameters characterizing the oxygen clusters and the parameters of the host matrix: the effective spin-figure interaction constant D for the molecule in thematrix, the exchange parameter J, and the number of pair clusters Np , which can deviate markedly fromthe purely random value N = 6Nc2 (N is Avogadro`s number, and c is the molar concentration of the impurity). The data on the magnetic susceptibility may be used to analyze the character of the positional and orientational short-range order in the solid solution. The value of D contains information about theorientational order parameter; the distance and angular dependence of the exchange interaction parameter is still a subject of discussion in the literature. The tempearture dependence of Npcontains information about diffusion and clusterization processes in the system.